Crystal engineering of quercetin via combined adsorption of polyvinylpyrrolidone and tannin - Kim, Jeongeun; Kwon, O. Pil; Lee, Jonghwi (Korean Journal of Chemical Engineering, 2023)
In nature, the structures and properties of biominerals are frequently precisely and synergistically controlled by two types of additives. However, the combination of two different types of additives has not often been thoroughly examined in the context of chemical, pharmaceutical, and biological crystallization. A combination of a polymeric additive, polyvinylpyrrolidone (PVP), and a low-molecular-weight additive, tannin (TA), was employed to explore the potential for crystal engineering with quercetin as an active compound. The nucleation time was significantly decreased by the additives, and the resulting crystals contained significant amounts of PVP and TA. FTIR spectroscopy analysis was used to confirm the specific molecular interaction between quercetin, PVP, and TA, and the results were consistent with the results of broadened peaks of XRPD, which indicated decreased particle size and aspect ratio. The melting point of quercetin was significantly depressed as the heat of fusion decreased. When two or more additives are combined, it is possible to obtain crystals with properties and structures that cannot be obtained by regular crystallization.
Keywords: Crystallization; Mesocrystal; Polyvinylpyrrolidone; Quercetin; Tannin